Adverse selection in a community-based health insurance scheme in rural Africa: Implications for introducing targeted subsidies - Parmar Divya; Souares Aurélia; de Allegri Manuela; Savadogo Germain; Sauerborn Rainer (BMC, 2012)
Abstract Background Although most community-based health insurance (CBHI) schemes are voluntary, problem of adverse selection is hardly studied. Evidence on the impact of targeted subsidies on adverse selection is completely missing. This paper investigates adverse selection in a CBHI scheme in Burkina Faso. First, we studied the change in adverse selection over a period of 4 years. Second, we studied the effect of targeted subsidies on adverse selection. Methods The study area, covering 41 villages and 1 town, was divided into 33 clusters and CBHI was randomly offered to these clusters during 2004-06. In 2007, premium subsidies were offered to the poor households. The data was collected by a household panel survey 2004-2007 from randomly selected households in these 33 clusters (n = 6795). We applied fixed effect models. Results We found weak evidence of adverse selection before the implementation of subsidies. Adverse selection significantly increased the next year and targeted subsidies largely explained this increase. Conclusions Adverse selection is an important concern for any voluntary health insurance scheme. Targeted subsidies are often used as a tool to pursue the vision of universal coverage. At the same time targeted subsidies are also associated with increased adverse selection as found in this study. Therefore, it's essential that targeted subsidies for poor (or other high-risk groups) must be accompanied with a sound plan to bridge the financial gap due to adverse selection so that these schemes can continue to serve these populations.